Fertility and Population Policy - Abdoulaye Ouedraogo; Mehmet S. Tosun; Jingjing Yang (Global Labor Organization (GLO), 2018)
There have been significant changes in both the fertility rates and fertility perception since 1970s. In this paper, we examine the relationship between government policies towards fertility and the fertility trends. Total fertility rate, defined as the number of children per woman, is used as the main fertility trend variable. We use panel data from the United Nations World Population Policies database, and the World Bank World Development Indicators for the period 1976 through 2013. We find significant negative association between a country's fertility rate and its anti-fertility policy. On the other hand, there is no significant and robust relationship between the fertility rate and a country's pro-fertility or family-planning policies. In addition we find evidence of spatial autocorrelation in the total fertility rate, and spatial spillovers from government's policy on fertility.
Keywords: H10; H59; J11; J13; J18; 330; fertility rate; population; government policies